قرآن مجید کی پیشن گوئیاں: تاریخی و جدید علمی تناظر میں ایک تحلیلی جائزہ: Prophecies of the Future in the Holy Qur’an: A Modern Scholarly & Historical Study - Abdullah Bodla, Muhammad; Ayaz Qureshi, Dr. Hafsah; Hussain, Malik Akhtar (Al-Amīr Research Journal for Islamic Studies, 2024)
The article explores the prophetic elements within the Quran that relate to future events. This scholarly work delves into the intricacies of how the Quran, beyond being a religious text, serves as a source of guidance through its predictions about the future. The focus of the analysis is on specific verses that scholars and believers argue contain knowledge of future happenings, underscoring the divine nature of the text. The article begins with a historical overview of prophetic literature in Islamic tradition, establishing a foundation for understanding the Quran’s place within it. It categorically examines various predictions purportedly made in the Quran, ranging from cosmological phenomena to social changes and significant events that have occurred over the centuries. Each example is meticulously analyzed, with references to classical and contemporary Islamic scholarship to interpret these verses. Key discussions in the article include the interpretation of Qur’anic verses that are believed to predict scientific discoveries and major world events. Additionally, the article addresses the challenges of translating and interpreting predictive verses, considering linguistic nuances and the context in which these verses were revealed. It discusses the broader implications of these interpretations on the faith of believers and the scholarly discourse surrounding the predictive nature of sacred texts. The conclusion reflects on the impact of these prophecies on Islamic theology and on the broader conversation about religion and prophecy in the modern world. It raises questions about the role of divine foresight in contemporary faith and how these ancient predictions continue to resonate with or challenge modern believers and skeptics alike. Overall, the article offers a comprehensive and balanced examination of the prophetic aspects of the Quran, providing readers with insights into both the spiritual and intellectual dimensions of understanding future predictions within a religious framework. Keywords: Qur’anic Prophecies, Islamic Eschatology, Theological Prediction, Qur’anic Exegesis, Miracles in Quran.